The Prevalence, Causes And Effects Of Drug Use And Abuse On Performance Indicators Among Secondary School Students In Teso South Constituency, Kenya - Etyang Marygoretty; Winga Maureen Adhiambo (European Scientific Journal, ESJ, 2021)
The use of drugs has become more rampant today than at any other time. In learning institutions, especially secondary schools, the use of drugs has resulted in poor concentration in classwork, high rate of absenteeism and failure in exams leading to poor academic performance. The purpose of this study therefore was to: establish the prevalence of drug use among students in Teso South Constituency, establish the causes of drug use and identify the effects of drug use on academic performance indicators among secondary school students in Teso South Constituency.  The constituency has a total of 25 public secondary schools with a total of 8023 students. Krejcie and Morgan’s formula was used to select 192 students and data was collected from the field using questionnaires and later analyzed using percentages. Results indicate that 54.7%, 22.4%, 6.7%, 4.7% 4.2%, 3.1% of the students use Tobacco, Miraa, Cocaine, Tranquilizers, Kuber and Marijuana respectively. Also, the most influential causes of drug abuse among them were Peer influence at 90.1%, family background at 57.1% and availability of drugs at 30.8%. Lastly, 89.6% of the students had poor grades due to drug abuse alongside 78.6% of them affected by low concentration span and lack of interest in studies. The study, therefore, inferred that there is a high of drug ab prevalence use amongst secondary school students with family, peers as well as availability contributing to the onset of drug abuse.The study concluded that drug abuse interferes with academic performance indicators of secondary school students in Teso South Constituency.